Pengaruh perencanaan Pajak, kepemilikan Manajerial dan Ukuran Perusahaan terhadap Nilai Perusahaan - Myana, Try; Khasanah, Uswatun; Nuryati, Tutty (Rifa'Institute, 2023)
This study aims to conduct a literature review on the effect of tax planning, managerial ownership and company size on Company Value. This study presents theoretical foundations, other explanatory variables and research results from previous literature. The research data used quantitative with the literature review method. This study aims to determine the relationship between tax planning, managerial ownership and company size on company value by describing the phenomena that occur.